2020
DOI: 10.3390/medicina56040168
|View full text |Cite
|
Sign up to set email alerts
|

Role of Parents in Body Mass Reduction in Children with Obesity—Adherence and Success of 1-Year Participation in an Intervention Program

Abstract: Background and Objectives: Obesity in children and adolescents results in a number of serious health-related consequences necessitating early treatment. Support from family members and family-focused lifestyle interventions can improve effectiveness of the treatment. The aim of the study was to assess the effects of parental characteristics and family-based dietary habits on the adherence and success of a body mass reduction program in children with obesity included in a lifestyle intervention program after 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Most studies use BMI to determine obesity in children and adolescents [ 14 , 20 , 21 , 22 ]. However, there is difficulty to establish a clear criterion for young population when defining overweight and obesity through the BMI, since it cannot distinguish between lean and body fat.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies use BMI to determine obesity in children and adolescents [ 14 , 20 , 21 , 22 ]. However, there is difficulty to establish a clear criterion for young population when defining overweight and obesity through the BMI, since it cannot distinguish between lean and body fat.…”
Section: Introductionmentioning
confidence: 99%
“…Moderator Effects of Parent's and Children's Characteristics, Self-Efficacy, and SES Family support, which is dependent on the characteristics of the family, are important for children as they develop physically (Rahelić et al, 2020). Some studies have found that changes in children's weight can be predicted from changes in their parents' weight (Andriani et al, 2015;Ohri-Vachaspati, 2019).…”
Section: Socioeconomic Status (Ses) and Academic Performancementioning
confidence: 99%
“…For example, Dhaliwal et al (2014) did not find the child's weight status at baseline to be a significant predictor of short-term attrition, while reported that inactive children had significantly lower weight status (body mass index [BMI] z-scores) at baseline. Conversely, there is also a study that found no statistical differences between the sample characteristics of completers' and non-completers' groups (Rahelić et al, 2020). In this regard, some experts pointed out that using a categorical variable for assessing adherence (e.g., completers vs. non-completers) may mask the effect of the different doses of treatment received and increase the risk of data bias.…”
Section: Introduction and Aimsmentioning
confidence: 99%